Evaluation of the precision of different Delay-Doppler Processor (DDP) algorithms using CryoSat-2 data over open ocean. Issue 6 (15th September 2018) - Makhoul, Eduardo; Roca, Mònica; Ray, Chris; Escolà, Roger; Garcia-Mondéjar, Albert
Highlights: This paper compares the performance of different Delay-Doppler (L1B) processing baselines as applied to CryoSat-2 (CS-2) data. A very good noise performance is obtained with conventional CS-2 SAR ocean re-tracker (25–30 cm SWH). Integrated ACDC processing improves the noise performance compared to conventional processing (10–15 cm SWH ∼ 1.5 m). The CS-2 baseline shows better noise estimation in SWH compared to Sentinel-3 processing baseline. Similar results are achieved for nominal CS-2 and modified with no zeros in multi-looking. Abstract: This article explores the modification and inclusion of different algorithms within an in-house Delay-Doppler Processor (DDP) chain in order to understand their potentiality and the related impact in terms of geophysical retrievals' precision, when operating the synthetic aperture radar (SAR) mode of CryoSat-2 mission over open ocean. To do so, a flexible and tunable processing chain has been developed by isardSAT, being able to accommodate the different algorithms/options. Two different levels of analysis have been carried out. On one hand, the CryoSat-2 nominal SAR processing baseline is compared against the one considered in the state-of-the-art Sentinel-3 ocean topographic mission, and then, against a modified version of CS-2, where the samples set to zero by the processor on the stack are not included in the incoherent averaging. On the other, the integration of an advanced processing at stack level and based on the amplitude compensation and dilation compensation (ACDC) is evaluated within the CryoSat-2 DDP. A comparative study of the different DDP configurations is presented exploiting SAR full bit rate (FBR) data from CryoSat-2 over two regions in the central Pacific Ocean and the Agulhas box. Ad-hoc SAR ocean re-trackers are exploited to derive the geophysical parameters (sea surface height-SSH and significant wave height-SWH), such that the performance of the different baselines can be quantified in terms of precision, i.e., estimation noise.